Islamic Philanthropy and SDGs: Evidence from Zakat Institutions in North Sumatra, Indonesia - Indra Prawira; Andri Soemitra; Yenni Samri Juliati Nasution (Universitas Islam Negeri Ar-Raniry, 2026)
Islamic philanthropy has increasingly been recognized as a strategic instrument for advancing inclusive and sustainable development, particularly through zakat management aligned with the Sustainable Development Goals (SDGs). This study examines the integration of zakat institutions with SDG implementation in North Sumatra, Indonesia, with a focus on SDG 1 (No Poverty), SDG 2 (Zero Hunger), and SDG 3 (Good Health and Well-being). The research aims to formulate a strategic model of Islamic philanthropy that strengthens the contribution of zakat institutions to sustainable development. A qualitative research design was employed using the Analytic Network Process (ANP) to identify and prioritize strategic elements within zakat governance and implementation. Data were collected through in-depth interviews, observations, documentation, and ANP-based pairwise comparisons involving regulators, practitioners, and academics. The findings indicate that zakat possesses significant potential to support sustainable development; however, its effectiveness remains constrained by weak institutional governance, limited human resource capacity, inadequate digital infrastructure, fragmented coordination, and low public trust in formal zakat institutions. The study identifies five strategic domains requiring improvement: governance, program relevance, inter-institutional coordination, economic sustainability, and public awareness. The ANP results further reveal three major priorities for institutional strengthening, namely enhancing supervisory functions, expanding public education regarding institutional zakat, and empowering mustahik through vocational and spiritual development programs. These findings highlight the importance of institutional reform, digital transformation, and empowerment-oriented zakat management in positioning Islamic philanthropy as a sustainable socio-economic development mechanism. ABSTRAK - Filantropi Islam dan SDGs: Bukti dari Lembaga Zakat di Sumatera Utara, Indonesia. Filantropi Islam semakin diakui sebagai instrumen strategis dalam mendorong pembangunan yang inklusif dan berkelanjutan, khususnya melalui pengelolaan zakat yang terintegrasi dengan Tujuan Pembangunan Berkelanjutan (Sustainable Development Goals/SDGs). Penelitian ini menganalisis integrasi lembaga zakat dengan implementasi SDGs di Sumatera Utara, Indonesia, dengan fokus pada SDG 1 (Tanpa Kemiskinan), SDG 2 (Tanpa Kelaparan), dan SDG 3 (Kehidupan Sehat dan Sejahtera). Tujuan utamanya adalah merumuskan model strategis filantropi Islam yang mampu memperkuat kontribusi lembaga zakat terhadap pencapaian pembangunan berkelanjutan. Penelitian ini menggunakan pendekatan kualitatif dengan metode Analytic Network Process (ANP) untuk mengidentifikasi serta memprioritaskan elemen-elemen strategis dalam tata kelola dan implementasi zakat. Data dikumpulkan melalui wawancara mendalam, observasi, dokumentasi, serta perbandingan berpasangan berbasis ANP yang melibatkan regulator, praktisi, dan akademisi. Hasil penelitian menunjukkan bahwa zakat memiliki potensi signifikan dalam mendukung pembangunan berkelanjutan, namun efektivitasnya masih dihadapkan pada sejumlah tantangan, antara lain lemahnya tata kelola kelembagaan, keterbatasan kapasitas sumber daya manusia, infrastruktur digital yang belum optimal, kurangnya koordinasi antarlembaga, serta rendahnya tingkat kepercayaan publik terhadap lembaga zakat formal. Penelitian ini mengidentifikasi lima area strategis yang perlu diperkuat, yaitu tata kelola, relevansi program, koordinasi kelembagaan, keberlanjutan ekonomi, dan peningkatan kesadaran publik. Temuan ANP juga menegaskan tiga prioritas utama dalam penguatan kelembagaan, yakni peningkatan fungsi pengawasan, perluasan edukasi publik terkait zakat kelembagaan, serta pemberdayaan mustahik melalui pengembangan keterampilan dan pembinaan spiritual. Secara keseluruhan, temuan ini menegaskan pentingnya reformasi kelembagaan, transformasi digital, dan penguatan pendekatan pemberdayaan agar filantropi Islam dapat berperan optimal sebagai instrumen pembangunan sosial-ekonomi yang berkelanjutan.